2020
DOI: 10.2147/dddt.s269765
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ketamine Enhances Intranasal Dexmedetomidine-Induced Sedation in Children: A Randomized, Double-Blind Trial</p>

Abstract: Purpose: To compare the efficacy of intranasal dexmedetomidine and dexmedetomidineketamine premedication in preschool children undergoing tonsillectomy. Patients and Methods: We enrolled 66 children with American Society of Anesthesiologists physical status I or II, aged 3-7 years undergoing tonsillectomy. Patients were randomly allocated to receive intranasal premedication with either dexmedetomidine 2 μg kg −1 (Group D) or dexmedetomidine 2 μg kg −1 and ketamine 2 mg kg −1 (Group DK). The primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
2
12
0
2
Order By: Relevance
“…A rising trend was observed in the onset time concerning age in our study. This onset time was similar to that of Sun’s study (9.6 min) in children between 1 month and 36 months ( 39 ) but shorter than those of other studies on intranasal dexmedetomidine combinations with intranasal/oral ketamine (15–17 min) in children between 0 months and 7 years old ( 14 , 25 , 26 , 31 ). Compared with propofol, this dexmedetomidine-midazolam regimen is time-consuming and requires appropriate time allotment in a high-patient-volume setting.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A rising trend was observed in the onset time concerning age in our study. This onset time was similar to that of Sun’s study (9.6 min) in children between 1 month and 36 months ( 39 ) but shorter than those of other studies on intranasal dexmedetomidine combinations with intranasal/oral ketamine (15–17 min) in children between 0 months and 7 years old ( 14 , 25 , 26 , 31 ). Compared with propofol, this dexmedetomidine-midazolam regimen is time-consuming and requires appropriate time allotment in a high-patient-volume setting.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, patients can be easily and unpredictably aroused by sounds or movements, which always cause serious interruptions in the MRI and prolong examinations in a busy setting ( 23 ). The addition of intranasal/oral ketamine can enhance intranasal dexmedetomidine-induced sedation efficacy and shorten sedation onset time ( 25 , 26 ). However, this regimen is associated with a large volume of intranasal administration.…”
Section: Discussionmentioning
confidence: 99%
“…However, our analysis found that, when nebulized dexmedetomidine was combined with oral or nebulized ketamine, it achieved better sedation and more frequently facilitated the separation from parents. This is consistent with the conclusion of Qian’s research ( 27 ). Dexmedetomidine produces sedative, analgesic, and anti-sympathetic effects by acting on α2 receptors on locus coeruleus ( 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, if the UMSS score of the child did not reach 2 points for more than 40 min, we recorded a satisfactory sedation time of 40 min. This may be the reason that the time to satisfactory sedation in the DS group was significantly shorter than that in the S group (p 0.001 < 0.05).Bin Qian et al compared intranasal dexmedetomidine (2 μg/kg) and dexmedetomidine combined with ketamine (DEX 2 μg/kg + KET 2 mg/kg) for tonsillectomy in preschool children and found that the median onset time of sedation (median) (15 vs 24 min) was significantly faster in the combination group than in the dexmedetomidine-alone group (Qian et al, 2020). In our study, the time to satisfactory sedation in Group D (median) was 23.5 min, which was similar.…”
Section: Discussionmentioning
confidence: 99%